2010
DOI: 10.1007/s10552-010-9524-7
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy characteristics and maternal breast cancer risk: a review of the epidemiologic literature

Abstract: The short- and long-term effects of pregnancy on breast cancer risk are well documented. Insight into potential biological mechanisms for these associations may be gained by studying breast cancer risk and pregnancy characteristics (e.g., preeclampsia, twining), which may reflect hormone levels during pregnancy. To date, no review has synthesized the published literature for pregnancy characteristics and maternal breast cancer using systematic search methods. We conducted a systematic search to identify all pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 165 publications
(332 reference statements)
1
75
2
Order By: Relevance
“…Women with preeclampisa have in some studies been found to be characterized by having a different hormonal profile than women with normotensive pregnancies. Among these differences are lower levels of estrogens and higher levels androgens and progesterone [26]. Reduced estrogen is thought to protect against breast cancer development, and increased progesterone Table 2 Breast cancer events, person-years at risk, and incidence rate ratio (IRR) with belonging 95% confidence interval of breast cancer according to preeclampsia and birth characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with preeclampisa have in some studies been found to be characterized by having a different hormonal profile than women with normotensive pregnancies. Among these differences are lower levels of estrogens and higher levels androgens and progesterone [26]. Reduced estrogen is thought to protect against breast cancer development, and increased progesterone Table 2 Breast cancer events, person-years at risk, and incidence rate ratio (IRR) with belonging 95% confidence interval of breast cancer according to preeclampsia and birth characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, human chorionic gonadotropin [27] and alfa-feto protein [28] may be elevated in women with preeclampsia. Both hormones are thought to be protective against development of breast cancer by inhibiting tumor progression [27] and by acting in an antagonistic way on estrogen effects in breast tissue [26]. One study, however, showed that estrogen concentration did not differ in women with preeclampsia compared with healthy women, but found significantly higher androgen levels in women with preeclampsia [29].…”
Section: Discussionmentioning
confidence: 99%
“…A Scottish cohort study of 753 pregnant women who underwent glucose testing at 13 weeks of pregnancy calculated a positive association between higher glucose levels and an increased risk of breast cancer diagnosed up to 20 years later [21]. An elevated risk was also observed among Israeli women with a history of GDM diagnosed with breast cancer at age 50 and above [24]. In contrast, a population-based case-control study of women first diagnosed before 35 years of age indicated an inverse association with breast cancer (OR: 0.54, 95% CI: 0.37-0.79) [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, findings have been inconsistent [24], possibly due to methodological limitations such as the use of self-reported information on GDM status and relatively small study populations. The main goal of the current historical cohort study was to evaluate the risk of malignancy among women diagnosed with GDM in a large health maintenance organization (HMO) in Israel using its automated clinical databases.…”
Section: Introductionmentioning
confidence: 99%
“…Younger age at first birth, multiple gestation pregnancies (twins and greater), preeclampsia, pre-pregnancy obesity, and gestational hypertension may all lower maternal breast cancer risk (reviewed by [33,34]), while increased placental weight [35], higher infant birth weight [34], and DES exposure during pregnancy are associated with increased risk of maternal breast cancer. One factor driving these changes is total lifetime exposure to ovarian hormones.…”
Section: Human Evidencementioning
confidence: 99%